Maternal biomarkers for early prediction of the neural tube defects pregnancies. Issue 7 (13th November 2020) - Yadav, Upendra; Kumar, Pradeep; Rai, Vandana
Abstract: Background: Neural tube defects (NTD) are one of the most common congenital birth defects. The reason for the NTD cause is still not completely known, but it is believed that some genetic and environmental factors might play a role in its etiology. Among the genetic factors the polymorphism in the folate gene pathway is crucial. Numerous studies have suggested the possible role of maternal higher plasma concentration of homocysteine and low concentration of folate and cobalamin in the development of NTD but some negative studies are also published. Aim: Aim of the present was to find out the exact relation between NTD and maternal biomarkers like folate, cobalamin and homocysteine by conducting a meta‐analysis. Method: Different electronic databases were searched for the eligible studies. Standardized mean difference (SMD) with 95% confidence interval (CI) was used to determine association between maternal markers as risk for NTD pregnancy. The p value <0.05 was considered statistically significant in all tests. All the statistical analyses were done in the Open Meta‐Analyst program. Results: The homocysteine is significantly associated with the increased risk of NTD (SMD = 0.57; 95% CI: 0.35−0.80, p = <0.001; I2 = 93.01%), s‐folate showed protective role in NTD (SMD = −0.48; 95% CI: −0.77 to −0.19, p = 0.001; I2 = 95.73%), similarly cobalamin is also having protective role (SMD = −0.28; 95% CI: −0.43 to −0.13, p = <0.001; I2 = 80.40%). Conclusion: In conclusion this study suggest that different maternal biomarkers may be used for the early prediction of the NTDs.